Traffic Responsive Control of Intersections with Predicted Arrival Times: A Markovian Approach. (11th June 2013) - Haijema, René; Hendrix, Eligius M. T.; Waller, S. Travis; Bhat, Chandra
Abstract The dynamic adaptive control of traffic lights can be formulated as a Markov decision problem (MDP). This framework is hardly used, as solving an MDP can be very time‐consuming and is only possible for simple infrastructures with a small number of traffic flows. Nevertheless, we show that the MDP framework can be used to construct control policies that approximately minimize the long‐run average waiting time at intersections. The MDP‐based approach is fast and thus allows real‐time use of actual information on traffic conditions, like queue lengths and the arrival times of near‐future arrivals. Simulation of an isolated intersection as well as a small network shows that the new policies with arrival information improve pretimed as well as exhaustive control. The new control policies and underlying algorithms scale up well to control networks.